PENERAPAN ICE BREAKING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SDN BAJANGREJO - Alifah, Furi; Sugeng Eko Putro Widoyoko; Nurhidayati (STKIP Subang, 2026)
This study aims to determine the results of implementing ice breaking in improving the learning motivation of third-grade students at SDN Bajangrejo. This research uses Classroom Action Research (CAR) with the Kurt Lewin model, which includes four stages: planning, implementation, observation, and reflection. The subjects of this study were 13 third-grade students. Data were collected through observation, interviews, and questionnaires, and analyzed using qualitative and quantitative data analysis techniques. The results showed an increase in students’ learning motivation, indicated by the average score rising from 1.6 in the pre-cycle (low category), to 2.6 in Cycle I (moderate category), and reaching 3.5 in Cycle II (high category). The use of ice breaking created a more lively and enjoyable learning atmosphere, making students more enthusiastic, active, and able to remember the material more easily. Therefore, ice breaking can be an effective learning strategy to improve students’ learning motivation in elementary school